Organizational and Individual Antecedents of Resistance to Change: Organizational Climate and Technology Readiness - Tatli Hasan Sadik; Eyitmiş Ahmet Melih; Zümrüt Muhammet Zeki (Organizacija)
There is interest in barriers to change in organizations. This research discusses factors affecting resistance to change based on employees’ technological competencies. This research aims to determine the mediating role of technology readiness in the effect of organizational climate in health institutions on resistance to change.